Change in land use and vegetation associated with lack of public services and public politics in Atoyatempan, Puebla (Nexo Revista Científica, 2021)
The present work aims to analyze the changes in land use in the municipality of Atoyatempan that occurred in the period from 1993 to 2014, by means of transition matrices and Markov chains, establishing their permanence or transition to another land use, using as a base the maps of land use and vegetation of the National Institute of Statistic and Geography (INEGI). The regions with the presence or not of public services are also specified, by means of the areas of influence to determine the lack of public services, and their relationship with the lack of public politics through a bivariate analysis, based on the survey for convenience made to the settlers. The results show the transition from natural vegetation and rainfed agriculture to grassland induced and irrigated agriculture by livestock activities. The areas with the lack of public services and their relationship with the lack of public politics are also specified, which will allow the development of more efficient solutions to stop the deterioration of the environment and improve the quality of life of the population.